Analysis of the Influence of Government Coordination on Development Planning in Padangsidimpuan City - Sihombing, Edi Epron; Sihombing, Marlon; Negara, Satia; Rini, Endang Sulistya (International Conference on Sciences Development and Technology, 2023)
The purpose of this study is to examine how government involvement affects the planning of Padangsidimpuan City's development. This study uses a cross-sectional survey method and an analytical observational approach. Sorting and managing activities are done using improvement and government participation. The Padangsidimpuan City Government's Territorial Device Organization consists of a population and investigation unit. The main research method used in this study is quantitative research. Specifically, the method used could be a cross-sectional study design. The Slovin Design was used to conduct the test, which is a systematic random sampling method. 330 individuals participated in this survey as respondents. The method used to examine the information is called data analysis. A way investigation is a method used to examine the relationships between different factors. It is a type of statistical modeling that allows analysts to test hypotheses about direct and indirect effects of one variable on another. According to the study, the development planning of Padangsidimpuan City is significantly influenced in a positive way by government involvement